ALD‐Coated Mesoporous Iridium‐Titanium Mixed Oxides: Maximizing Iridium Utilization for an Outstanding OER Performance. Issue 6 (27th January 2022) - Frisch, Marvin; Raza, Muhammad Hamid; Ye, Meng‐Yang; Sachse, René; Paul, Benjamin; Gunder, René; Pinna, Nicola; Kraehnert, Ralph
Abstract: With the increasing production of renewable energy and concomitant depletion of fossil resources, the demand for efficient water splitting electrocatalysts continues to grow. Iridium (Ir) and iridium oxides (IrO x ) are currently the most promising candidates for an efficient oxygen evolution reaction (OER) in acidic medium, which remains the bottleneck in water electrolysis. Yet, the extremely high costs for Ir hamper a widespread production of hydrogen (H2 ) on an industrial scale. Herein, the authors report a concept for the synthesis of electrode coatings with template‐controlled mesoporosity surface‐modified with highly active Ir species. The improved utilization of noble metal species relies on the synthesis of soft‐templated metal oxide supports and a subsequent shape‐conformal deposition of Ir species via atomic layer deposition (ALD) at two different reaction temperatures. The study reveals that a minimum Ir content in the mesoporous titania‐based support is mandatory to provide a sufficient electrical bulk conductivity. After ALD, a significantly enhanced OER activity results in dependency of the ALD cycle number and temperature. The most active developed electrocatalyst film achieves an outstanding mass‐specific activity of 2622 mA mgIr –1 at 1.60 VRHE in a rotating‐disc electrode (RDE) setup at 25 °C using 0.5 m H2 SO4 as a supporting electrolyte. Abstract : A new concept for the design of highly active electrocatalysts for acidic oxygen evolution reaction (OER) based on mesoporous iridium titania support (Ir0.15 Ti0.85 O2 ) films surface‐modified with ultra‐thin IrO x layers via conformal atomic layer deposition (ALD) is described, leading to a significantly improved noble metal utilization.